G465(P) Improving blood glucose control in young people with type 1 diabetes – What factors are perceived as helpful?. (27th April 2016) - Selvadurai, L; Chivers, SC; Cassidy-Kojima, C; Woods, S; Holloway, E
Abstract : Background and aims: Within our organisation 115 children and young people have a diagnosis of type 1 diabetes mellitus. In March 2014, a new multidisciplinary service commenced, and use of electronic download (Diasend™) began for glucometers during clinic visits, in the light of new best practice for diabetes mellitus. Aim: Identify patients with improved diabetes control and factors which have contributed. Method: 35 patients with established type 1 diabetes mellitus were identified. They had sustained (2 or more consistent HbA1c levels >3 months apart) improved control (>10% reduction in HbA1c) from March 2014 to September 2015 as our cohort. A telephone survey was then conducted asking 24 questions on a range of topics related to health and social factors that may influence diabetes control. Results: There were 20 respondents. Several questions were open and qualitative. Of the questions which generated a scored ranking three received most positive feedback: Reviewing blood glucose levels on the computer screen to discuss during clinic visits (100% of respondents thought helped, mean score of 8.2)Increased awareness of the complications of diabetes (100% of respondents, mean score 8.1)Increased blood glucose test frequency (75% of respondents, mean score 7.2) Qualitative response themes consistently mentioned healthy changes to diet to help control their blood sugar level (45%). Members of the diabetes team were mentioned in 35% of qualitative responses when asked what helped attendance to clinic appointments. Conclusion: All patients identified the ability to visualise blood glucose levels with the team during clinic consultations as helpful. Increased testing frequency, awareness of diabetes complications and openness were also positive factors in helping improve control. Surprising negative results were the lack of perceived benefit of smartphone apps such as carb counting and downloading at home. Qualitative data highlighted the importance of the multidisciplinary diabetes team and importance of a healthy diet to patients.